Efektivitas Strategi Self-Management untuk Menurunkan Kejenuhan Belajar pada Siswa Kelas XI-IPS 1 SMA Negeri 1 Kedamean Gresik - Aini Rizki Setyoisanti; Cindy Asli Pravesti (Universitas Kanjuruhan Malang, 2022)
Burnout is a condition in which a person experiences physical and emotional exhaustion due to the many demands of schoolwork, to determine a person's burnout level can be measured using emotional exhaustion, physical exhaustion, cognitive exhaustion, and loss of motivational memory using the burnout scale. . This research is useful in knowing that self-management strategies are very effective in reducing burnout in class XI IPS 1 students of SMAN 1 Kedamean. This study used a quantitative approach with the Single Subject Design (SSD) experimental design with A-B-A design. In collecting data, researchers used several analytical techniques, namely descriptive statistics and visual analysis techniques. The subjects in this study were 2 students of class XI IPS 1 with the highest level of learning saturation. The results of this study were that 2 students or subjects experienced a decrease in their initial pre-test scores. So that the results of the final ability post-test for PW subjects with a score of 35 and PDC subjects with a score of 36. These results can be concluded that the use of self-management strategies is effective in reducing student boredom at SMAN 1 Kedamean Gresik.